2016
DOI: 10.4191/kcers.2016.53.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Sol-Gel Derived Ho3+/Yb3+ Co-Doped NaCaGd(MoO4)3 Phosphors and their Upconversion Photoluminescence

Abstract: NaCaGd(MoO 4) 3 :Ho 3+ /Yb 3+ ternary molybdates were successfully synthesized by microwave sol-gel method for the first time. Well-crystallized particles formed after heat-treatment at 900°C for 16 h showed a fine and homogeneous morphology with particle sizes of 3-5 μm. Under excitation at 980 nm, the UC intensities of the doped samples exhibited strong yellow emissions based on the combination of strong emission bands at the 520-nm and 630-nm emission bands in the green and red spectral regions, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…As shown in Fig. 2(b energy transfer, which can be explained with the same theory [37][38][39]. Consequently, the intensity of green photoluminescence increases with increasing Yb 3+ content as shown in Fig.…”
Section: 대한금속 • 재료학회지 제57권 제9호 (2019년 9월)supporting
confidence: 62%
See 1 more Smart Citation
“…As shown in Fig. 2(b energy transfer, which can be explained with the same theory [37][38][39]. Consequently, the intensity of green photoluminescence increases with increasing Yb 3+ content as shown in Fig.…”
Section: 대한금속 • 재료학회지 제57권 제9호 (2019년 9월)supporting
confidence: 62%
“…Notably, photoluminescence intensity decreased when going from 2 mol% to 3 mol% Yb 3+ . This is attributed to the enhancement of non-radiative transitions caused by interactions between Yb 3+ ions at high Yb content [38]. Figure 9 shows that, like the upconversion photoluminescence intensity, green and red emission intensities increased with increasing near-infrared excitation power.…”
Section: 대한금속 • 재료학회지 제57권 제9호 (2019년 9월)mentioning
confidence: 94%
“…Твердые растворы CaMoO 4 −NaGd(MoO 4 ) 2 (CMO−NGM) экспериментально изучались в работах [10][11][12]. В синтезированные золь-гель методом с последующей прокалкой поликристаллические образцы тройного молибдата NaСаGd(MoO 4 ) 3 вводились ионы Er 3+ и Yb 3+ [11] или Но 3+ и Yb 3+ [12], замещавшие до 50% ионов гадолиния. В этих работах было установлено, что, как номинально чистый NaСаGd(MoO 4 ) 3 , так и замещенные образцы тройного молибдата имели структуру шеелита.…”
Section: Introductionunclassified
“…CaMoO 4 −NaGd(MoO 4 ) 2 (CMO−NGM) solid solutions were experimentally investigated in [10][11][12]. In polycrystalline samples of NaCaGd(MoO 4 ) 3 triple molybdate obtained by the sol-gel method and additionally annealed the Er 3+ and Yb 3+ [11] or Ho 3+ and Yb 3+ [12] were introduced, that substituted up to 50% of gadolinium ions. In these studies it was found that both nominally pure NaCaGd(MoO 4 ) 3 and substituted samples of triple molybdate had a structure of scheelite.…”
Section: Introductionmentioning
confidence: 99%